Cultivo de Dendrocephalus brasiliensis (Pesta, 1921) visando à aplicação em aquicultura - Silva, Ricardo Augusto Custodio da (Universidade Federal de São Carlos, 2016)
The hatchery is now the main obstacle of aquaculture. Live food, especially zooplankton, is essential in the first life stages of fish. However, there are difficulties in obtaining sufficient biomass. The Anostraca Dendrocephalus brasiliensis, known as “branconeta”, has great potential for use in national aquaculture. In this study, experiments were conducted in controlled conditions in order to obtain: I) the best conditions for hatching of resistant cysts, evaluating the cyst density in the sediment, temperature and pH of the water, and cysts dehydration time; II) identification of the early stages of life, focusing on the length and time to maturity, and we also investigate the main factors that influence the development of the early stages and; III) semiintensive production, the organisms were grown during winter and summer, with two different diets and subsequent analysis of the biochemical composition of organisms grown in these conditions. Hatching occurs in low proportions, and is mainly influenced by the density of cysts present in the sediment, and show some tolerance to different levels of temperature and pH. The average time to reach adulthood was ten days and during the early stages, we observed that some individuals have delayed hatching. Among the environmental variables, temperature and conductivity play a major role in the growth during this period, along with the food, which must be provided from the third day. In semi-intensive farming conditions, we found that large amounts of food promote greater growth in length, both in summer and winter, however, during the winter, low amounts of food provide greater survival. In biochemical analysis, individuals grown with a low amount of food had higher proportion of protein, values higher than those found in Artemia sp. We also detected the presence of polyunsaturated fatty acids, which are of great interest in organisms to be used as live food for fish. In general, D. brasiliensis can be regarded as a suitable species for use in aquaculture due to: ease handling of cysts, since cysts present in the sediment are sufficient for obtaining large populations; growth rate and high tolerance to ambient changes, not requiring great efforts in keeping the culture medium and; nutritional quality, with high concentration of proteins and the presence of polyunsaturated fatty acids.
Keywords: Larvicultura; Eclosão de cistos; Desenvolvimento; Taxa de crescimento; Composição bioquímica; Hatchery; Cysts hatching rate; Development; Growth rate; Biochemical composition; Thamnocephalidae; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA